Determinants of Self-esteem and Social Responsibility among Undergraduates of Dhaka City: Effects of Gender, Family Pattern and University Type - Akhter, Shayama; Hossain, Md Shakhawat (Journal of Business and Technology (Dhaka), 2013)
This paper is based on the results of a conducted study to investigate the level of self-esteem and social responsibility of the students of Bangladesh by the types of university, gender and family pattern. The sample of the study consists of 120 students where 60 students are from a public university and the remaining 60 students from a private university. In both cases, the 60 students are drawn as 30 male and 30 female. Of these two genders, 15 are from nuclear families and the other 15 from joint families. Therefore, there are total four levels of the public and private university students. The data are collected through questionnaires and analyzed by the analysis of variance. Results have revealed that self-esteem and social responsibility are significantly different according to the types of family pattern and gender while self-esteem differs by the types of university but social responsibility does not. DOI: http://dx.doi.org/10.3329/jbt.v6i2.14515 Journal of Business and Technology (Dhaka) VolVI, Issue02, (July-December, 2011) & VolVII, Issue-1 (January-June, 2012) pp.21-33